NÛR SÛRESİNİN KIRAATLER AÇISINDAN İNCELENMESİ - ÇİLOĞLU, EKREM (Fırat Üniveristesi, 2021)
Bu çalışma Nûr sûresinin kıraatler bakımından incelenmesini konu edinmektedir. Giriş kısmında kıraat çeşitleri, kıraat imamları ve Nûr sûresi hakkında bilgi verilmiştir. Ana konusu itibariyle Nûr sûresi hem sahih, hem de şâz kıraatler bağlamında incelenmiş ve ilk olarak sahih kıraatler esas alınarak âyetlerin anlamını etkileyen ve etkilemeyen kıraat farklılıkları tespit edilmiştir. Daha sonrasında şâz kıraat vecihleri usûl ve ferşî farklılıklar olarak incelenmiştir. Anahtar Kelimeler: Kur'ân, Nûr sûresi, Kıraat, Sahih, Şâz

This study focuses on the examination of Surah An-Nûr in terms of recitations. In the introduction, information was given about the types of recitation, imams of recitation and the surah of An-Nûr. In terms of it's main subject, Surah An-Nûr was examined in the context of both reality and precise recitations and firstly, based on precise recitations, differences in recitation that affect the meaning of verses were determined. Afterwards, the recitation laws were examined as procedural and Shâdhdh differences. Key Words: The Qur'an, Nûr Surah, Recitation, Reality, Shâdhdh
Examination of Surah Nûr in terms of recitations
Keywords: Din